Antibiotics and Antimicrobials Resistance: Mechanisms and New Strategies to Fight Resistant Bacteria - Cécile Muller (MDPI AG, 2022)
Antibiotics have revolutionized medicine over the past century and have helped to control most infectious bacterial diseases [...]